THE EFFECT OF CUSTOMER TRUST, BRAND IMAGE, AND SERVICE QUALITY ON CUSTOMER LOYALTY OF AIRLINES E-TICKET SERVICE (A STUDY ON TRAVELOKA) - Tumewu, Andreas Markus; Pangemanan, Sifrid; Tumewu, Ferdinand (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: The development of information technology has now entered the digital era where all forms of information can be accessed so quickly and easily through the mobile. Therefore the people requires a good media that can provide enough information to perform the selection against different types of airlines offer to be used as a tool to support decision making on buying airlines e-tickets,The aims of this study are to analyze the effect of customer trust, brand image and service quality on customer loyalty of Traveloka. This research is causal type of research which uses primary data obtained through questionnaires and uses multiple regression analysis. The population observed is people in Manado who have experiences with Traveloka, The sample size is 100 respondents.The result of this study shows that customer trust has partially affected on customer loyalty, brand image has not partially affected on customer loyalty and service quality has partially affected on customer loyalty. Traveloka should have a good quality based on customer perception not only focus on building their brand image as a site booking number one because it has no significant effect to customer loyalty.Keywords: customer trust, brand image, service quality